Menilai Keterampilan Mencatat, Meringkas dan Kemampuan Interpersonal Peserta Didik di Sekolah Menengah Atas - Tryas Amanda Putri; Rika Kurniawati; Tesa Amilia Putri; Muhammad Luthfi Fauzan; Romi Fajar Tanjung; Khadijah Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to understand how note-taking skills, summarizing skills, and interpersonal relationships can enhance the quality of learning and student motivation at SMAN 02 Indralaya Utara. The research will investigate how the application of note-taking skills can increase student motivation, how summarizing skills can help students understand their feelings, and how interpersonal relationships can increase students' awareness of learning problems they face. In this study, students' note-taking and summarizing skills were analyzed quantitatively using a questionnaire technique, with results from 37 respondents showing that most students' note-taking skills were mostly average, while most students' summarizing skills were mostly average and high, indicating that students' interest and desire to record lesson material significantly helps in understanding material already explained by the teacher, and that note-taking and summarizing skills are important skills in the learning process and need to be enhanced through more intensive guidance and practice. Lastly, interpersonal relationships were mostly average, with some students having high levels and others having low levels. Although there were some respondents in the low category, overall, the results can be concluded to be relatively good.